Clavis: A New Selection and Gradation to Accelerate a Comprehensive Para-Tenses Mastery - Jaelani Jaelani (Humanitatis : Journal of Language and Literature, 2023)
This study delves into the effectiveness of the Clavis Selection and Gradation approach in teaching English as a Foreign Language (EFL). Grounded in the theories of Richards (2017) and Faravani & Zeraatpishe (2016), which underscore the significance of grammar selection and gradation, this research employs a mixed-methods approach to address its objectives comprehensively. Two distinct groups of English teacher trainees from Universitas Islam Negeri Mataram are strategically selected for the study, with one group undergoing the Clavis Selection approach. At the same time, the other follows the conventional scheme. Data collection encompasses Pre-Test and Post-Test assessments and open-ended interviews. The assessments cover various grammatical aspects, and both groups receive treatment through five sessions. By integrating quantitative and qualitative data analysis, this study aims to provide a nuanced understanding of the Clavis Selection approach's impact on EFL learners, contributing to the field of language education. Pre- and Post-Test assessments, coupled with open-ended interviews, reveal that the Clavis Selection approach significantly improves learners' grammar proficiency compared to conventional methods. This mixed-methods research advances our understanding of grammar instruction and underscores the relevance of systematic selection and gradation in EFL pedagogy.